The restless universe : understanding X-ray astronomy in the age of Chandra and Newton - Schlegel, Eric M. (Eric Matthew), 1954- (Oxford University Press, 2002)
A research astrophysicist at the Smithsonian Astrophysical Observatory offers an engaging introduction to the exciting field of x-ray astronomy. 62 halftones, 31 line illustrations, & 7 color images.